Religion and National Multiculturalism in Indonesian Religious Higher Education: Negotiating Diversity, Democracy, and Social Cohesion - Edi Safitri; Ahmad Asroni (JUMPA : Jurnal Manajemen Pendidikan, 2025)
Growing concerns over the weakening of national cohesion, the expansion of intolerant attitudes, and the emergence of exclusive religious perspectives have renewed discussions on multiculturalism within Indonesian higher education. This study examines how religious higher education institutions construct national multiculturalism and negotiate religious values in strengthening democracy, tolerance, and social cohesion. The research was conducted at Universitas Islam Indonesia, Sanata Dharma University, and Satya Wacana Christian University as representatives of religion-based universities with different religious traditions. Employing a qualitative approach, data were collected through observation, in-depth interviews, documentation, and Focus Group Discussions, then analyzed through coding, cross-case comparison, and interpretive analysis. Findings indicate that the three universities position multiculturalism not only as a social reality but also as an educational and ethical foundation for sustaining inclusive citizenship. Universitas Islam Indonesia develops an inclusive Islamic orientation through religious moderation and the integration of Islamic and national values. Sanata Dharma University advances a humanistic and dialogical model through interfaith engagement and shared social experiences. Satya Wacana Christian University strengthens pluralism through its institutional identity as a “Mini Indonesia” that promotes democratic interaction and social solidarity. Across these contexts, multicultural values are translated into character education, interreligious dialogue, inclusive academic practices, and non-discriminatory campus life. The study concludes that religious higher education institutions hold a strategic role in cultivating multicultural citizenship and demonstrates that the relationship between religion and multiculturalism in Indonesia is more accurately understood through a model of religious accommodation than secular separation.